Diseño de un plan de mejoramiento integral por procesos para la empresa COVIPROV perteneciente al gobierno provincial de Pichincha, ubicada en la ciudad de Quito - Rodríguez Chiliquinga, Harold Patricio (2014)
The phenomena of globalization have led to a strengthening of competitiveness in all sectors of the economy. This means that, increasingly, suppliers of goods and services are required to maintain set his sights on quality and continuous improvement to be chosen by customers. The range of choice, advertising, the influence of the media, higher levels of information and education customers, the demonstration effect that is triggered from more advanced economies, the rise of consumer leagues, tuning laws that establish rights, in short, all the changes that have been raising especially since the seventies, have made, every day, consumers are more selective when choosing their suppliers (Crosby, 1989).